2004
DOI: 10.1128/aem.70.6.3298-3304.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Nucleotide Sequence, and Overexpression of the l -Rhamnose Isomerase Gene from Pseudomonas stutzeri in Escherichia coli

Abstract: The gene encoding L-rhamnose isomerase (L-RhI) from Pseudomonas stutzeri was cloned into Escherichia coli and sequenced. A sequence analysis of the DNA responsible for the L-RhI gene revealed an open reading frame of 1,290 bp coding for a protein of 430 amino acid residues with a predicted molecular mass of 46,946 Da. A comparison of the deduced amino acid sequence with sequences in relevant databases indicated that no significant homology has previously been identified. An amino acid sequence alignment, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 37 publications
0
38
1
Order By: Relevance
“…Two isomerases that prefer deoxy-sugars as their substrates are L-fucose isomerase [21,47] and L-rhamnose isomerase [57,58]. These enzymes also tolerate other modifications at centers higher than C3 and can use epimeric or functionalized sugars as substrates.…”
Section: Isomerases For Deoxygenated and Other Modified Sugarsmentioning
confidence: 98%
“…Two isomerases that prefer deoxy-sugars as their substrates are L-fucose isomerase [21,47] and L-rhamnose isomerase [57,58]. These enzymes also tolerate other modifications at centers higher than C3 and can use epimeric or functionalized sugars as substrates.…”
Section: Isomerases For Deoxygenated and Other Modified Sugarsmentioning
confidence: 98%
“…5 L-Rhamnose isomerase from Pseudomonas stutzeri (P. stutzeri L-RhI; Swiss Prot accession number Q75WH8, 430 amino acid residues, 46,975 Da) 6 shows a broader substrate specificity than L-RhI from Escherichia coli (E. coli L-RhI; Swiss Prot accession number P32170, 419 amino acid residues, 47,199 Da) 2 , catalyzing the isomerization between various aldoses and ketoses, as well as between L-rhamnose and L-rhamnulose, in the presence of appropriate metal ions. [5][6][7] Leang et al reported that a recombinant His-tagged P. stutzeri L-RhI efficiently catalyzed the isomerization between L-rhamnose and L-rhamnulose, L-mannose and L-fructose, L-lyxose and L-xylulose, D-ribose and D-ribulose, and D-allose and D-psicose, as listed in Figure 1(a) with the enzyme activities. Since some of them are so-called "rare sugars" which exist in small amounts in nature, P. stutzeri L-RhI is exploited for industrial applications in rare sugar production.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperatures and half-lives of RhaAs from the mesophiles E. coli, P. stutzeri, and B. pallidus are 60, 60, and 65°C, respectively, and as 10 min at 50°C, 10 min at 60°C, and 60 min at 60°C, respectively (Badia et al 1991;Leang et al 2004c;Poonperm et al 2007b). However, RhaA from the hyperthermophile T. maritima examined in this study has an optimum of 85°C and a half-life of 773 h at 75°C, which is 773 times higher than that from B. pallidus RhaA at 60°C.…”
Section: Resultsmentioning
confidence: 98%